Diagnóstico de salud bucodental y factores de riesgo en los centros educativos primarios Pérez Tagle, Rosa Matilde Alvear, Luis Pasteur, López de León, Leopoldo Nicolás Chávez, Mercedes Alcira Palacios de Carpio de la parroquia Santiago del cantón Loja, año 2013 - Guarnizo González, Karina Melissa (2013)
The oral diseases are a major problem in our country and in the South is an important index so Loja Canton is not exempt from this reality in both its rural and urban parishes. The research work aims to make the diagnosis center oral health of students in primary schools "TAGLE PEREZ", "ROSA MATILDE ALVEAR”, "LOUIS PASTEUR”, "LOPEZ DE LEON" , "NICK CHAVEZ LEOPOLDO" , "MERCEDES ALCIRA CARPIO PALACES" of Loja Canton Santiago parish . This project is descriptive, prospective, cross-sectional, we worked with 148 elementary school students. With the following results: 95.9% caries present in 64.2% gingival inflammation, gingival bleeding 10.1% and 11.5 % had altered occlusion. It was found that within the habits that affect the population is mouth breathing and tongue thrusting, and within the pathologies that are most often affect premature loss of primary teeth and anterior crossbite, 7.4% showed the presence of mild fluorosis. The results were collected through a survey and History Dental Clinic, showing that the whole group showed abnormal examined his mouth. Keywords: oral health, risk factors, dental caries, gingival inflammation.